1973
DOI: 10.1097/00000658-197310000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Single Lung Transplantation in Experimental and Human Emphysema

Abstract: HE RESULTS of single lung transplantation in patients with severe pulmonary emphysema have been poor. Most of the patients have died within a few weeks of operation from respiratory insufficiency produced mainly by a serious ventilation-perfusion (V/Q) imbalance.21,22,30 The latter has been characterized by underventilation of the transplant despite the fact that it has been receiving most of the pulmonary blood flow.19 Because the classic histologic manifestations of rejection were not present in the allograf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

1974
1974
2013
2013

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(21 citation statements)
references
References 19 publications
0
21
0
Order By: Relevance
“…Subsequent studies showed that ventilation/perfusion alterations are not constant and are usually associated with characteristic alterations of the graft [10,11] such as rejection, infection or reimplantation injury. Furthermore, hyperinflation of the native lung causes graft compression, but only when the function of the newlyimplanted lung is impaired.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies showed that ventilation/perfusion alterations are not constant and are usually associated with characteristic alterations of the graft [10,11] such as rejection, infection or reimplantation injury. Furthermore, hyperinflation of the native lung causes graft compression, but only when the function of the newlyimplanted lung is impaired.…”
Section: Discussionmentioning
confidence: 99%
“…The use of plication [1,16], local excision [14], segmental resection [17], lobectomy [13] and even lung transplantation [18] have been reported, with variable results [1,[13][14][15][16][17][18]. The resection of giant bullae might be viewed as a special case of lung volume reduction in severe emphysema; in both instances the principle is to reduce lung volume by resecting the worst functioning lung tissue.…”
Section: Discussionmentioning
confidence: 99%
“…4 Similarly, we believe that singlelung transplantation for patients with cystic fibrosis or other forms of chronic pulmonary sepsis is not advisable, as persistent infection in the remaining, native lung would pose a significant hazard, especially in the immunosuppressed recipient. We have not considered single-lung transplantation for patients with emphysema, out of concern that the remaining, native lung would hyperexpand, resulting in crowding of the transplanted lung.…”
Section: Follow-up Evaluationmentioning
confidence: 99%